Retention of CAD PEEK versus metallic partial denture frameworks in patients with mandibular Kennedy Class I - Amr Magdy Ibrahim Abdelaziz; Mohamed Amr ElKhashab; Azza Hussein Zaky (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Traditionally, removable partial denture (RPD) frameworks have been made from metal alloys, with patients expressing dissatisfaction regarding esthetics, metallic taste, and weight. Several attempts have been made to introduce new materials suitable for RPD frameworks. Purpose: This study aims to compare the retention of polyetheretherketone (PEEK) and metallic computer-aided designed (CAD) removable partial dentures (RPD) in patients with mandibular Kennedy Class I. Methods: Twenty-four patients with Kennedy Class I partially edentulous mandibles were randomly assigned to two parallel groups. Computer-aided design of the RPD’s frameworks was used to produce a sacrificial resin pattern, then cast into cobalt chromium (Co-Cr) or pressed into PEEK to produce RPD frameworks. An acrylic resin denture base and teeth were attached to the framework, processed, finished, polished, and delivered to the patients. Retention in Newtons was measured for both groups by pulling the RPDs from their geographic center at the time of insertion, after one and three months. Results: At each time interval, a repeated measures ANOVA revealed statistically significantly higher mean retention values for the metal group compared to the PEEK group. Retention did not decrease significantly in the PEEK group, whereas a significant retention decrease was observed in the metal group. An independent student’s T-test revealed a significant difference between retention loss for the metal and PEEK groups. Conclusion: Within the limitations of this study, although metal RPD frameworks provide higher mean retention values than PEEK RPD frameworks, both show clinically acceptable retention levels. Nevertheless, PEEK maintains retention more than metal in the short term.